Biologics for Ulcerative Colitis: Status of the Art and General Considerations - Giovanni Clemente Actis (Shiraz University of Medical Sciences, 2017)
Background: Expanding over Crohn’s disease in the Far East, and easily biased to chronicity, ulcerative colitis (UC) continues to pose a challenge. Traditional remedies have been based on control of inflammation and immune suppression, effected by such classic drugs as mesalamines, corticosteroids, and thiopurines. However, these molecules have long proven unable to fully controlthe disease or modify disease history, leaving an alternative fully desirable.Objectives: In this study, we aimed at highlighting the indications for biological therapy in UC.Methods: Literature review.Results: Recently, it has been demonstrated that the proinflammatory cytokine tumor necrosis factor (TNF) plays a significant role in UC, opening a way for anti-TNF biologics to join the therapeutic arsenal. These monoclonal antibodies, now available as hybrids or fully human preparations, are able to attain at least 50% response rate of refractory UC. However, primary non-response amountsto 20% - 40%, and loss of response to 40%. Optimization protocols allow for biologic molecule switching (disease symptoms, antibody positive) or replacement with another drug class (symptoms but no antibodies). Infectious/neoplastic /autoimmune toxicities together with high costs continue to be a problem (52%).Conclusions: These results warrant further therapeutic leaps forward: personalized therapy plans based on the patiens’ genetic profile, and pre-emptive measures based on people’s education to modify diet and life habits.